The Gayatri Mantra: A Comprehensive Analysis of Its Spiritual, Cultural, and Scientific Significance Through Vedic and Puranic Wisdom - Pallathadka, Harikumar; Roy, Parag Deb (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
This paper presents a comprehensive examination of the Gayatri Mantra, one of the most revered Sanskrit verses in Hindu tradition. Through detailed analysis of its historical origins, linguistic structure, spiritual significance, and contemporary applications, this study illuminates why this ancient verse has maintained its profound relevance across millennia. Drawing extensively from Vedic literature, Puranic texts, scholarly interpretations, and scientific research, this paper demonstrates how the Gayatri Mantra functions as a bridge between ancient wisdom and modern spiritual practice, offering insights into consciousness development, meditative practices, and holistic well-being. The integration of numerous Vedic and Puranic references provides an authoritative foundation for understanding the mantra's multidimensional significance, while established scientific research suggests potential psychophysiological effects that warrant further investigation.